Accountability for Criminal Acts of Child Abuse Committed by Children with a Restorative Justice Approach - Lafau, Karolus Kanefo; Simamora, Janpatar (Golden Ratio of Data in Summary, 2025)
Increasing violence against children causes public dissatisfaction. Moreover, the crimes were committed by those closest to him. In this case, resolving this problem requires a restorative justice approach that reconciles family relationships between parties. The aim of this research is to determine the legal aspects of the restorative justice approach to acts of sexual abuse committed by minors against minors and the restorative justice approach to acts of sexual abuse committed by minors against minors. The aim of this research is to determine the restorative justice approach to acts of sexual abuse against minors committed by minors. The research method used by the author is qualitative. The conclusion drawn is the first. The restorative justice approach carried out by the Attorney General's Office of the Republic of Indonesia and the Indonesian District Court judiciary towards criminal acts of sexual abuse against minors committed by minors aims to support the families of victims and minors. perpetrator's family to provide family counseling. Second, the legal perspective of the restorative justice approach adopted by law enforcement officers is consistent with the values of social norms that apply in society. Because basically family values teach us to forgive each other.